Hypersensitivity Induced by Intrathecal Bradykinin Administration Is Enhanced by N-oleoyldopamine (OLDA) and Prevented by TRPV1 Antagonist - Uchytilova, Eva; Spicarova, Diana; Palecek, Jiri (International journal of molecular sciences, 2021)
Transient receptor potential vanilloid 1 (TRPV1) channels contribute to the development of several chronic pain states and represent a possible therapeutic target in many painful disease treatment. Proinflammatory mediator bradykinin (BK) sensitizes TRPV1, whereas noxious peripheral stimulation increases BK level in the spinal cord. Here, we investigated the involvement of spinal TRPV1 in thermal and mechanical hypersensitivity, evoked by intrathecal (i.t.) administration of BK and an endogenous agonist of TRPV1, N-oleoyldopamine (OLDA), using behavioral tests and i.t. catheter implantation, and administration of BK-induced transient thermal and mechanical hyperalgesia and mechanical allodynia. All these hypersensitive states were enhanced by co-administration of a low dose of OLDA (0.42 µg i.t.), which was ineffective only under the control conditions. Intrathecal pretreatment with TRPV1 selective antagonist SB366791 prevented hypersensitivity induced by i.t. co-administration of BK and OLDA. Our results demonstrate that both thermal and mechanical hypersensitivity evoked by co-administration of BK and OLDA is mediated by the activation of spinal TRPV1 channels.
Keywords: dopamin; kationtové kanály TRPV; Spinal Cord; allodynia; mícha; krysa rodu Rattus; Hyperalgesia; zvířata; potkani Wistar; Bradykinin; Rats, Wistar; Male; spinal cord; Dopamine; bradykinin; Rats; hyperalgezie; TRPV1; TRPV Cation Channels; Animals; hyperalgesia; mužské pohlaví; OLDA; spinální injekce; Injections, Spinal